2016
DOI: 10.1016/j.jclepro.2016.03.120
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability analysis of the electric vehicle use in Europe for CO2 emissions reduction

Abstract: Electric vehicles are considered the most promising alternative to internal combustion engine vehicles towards a cleaner transportation sector. Having null tailpipe emissions, electric vehicles contribute to fight localized pollution, which is particularly important in overpopulated urban areas. However, the electric vehicle implies greenhouse gas emissions related to its production and to the electricity generation needed to charge its batteries. This study focuses the analysis on how the electric vehicle emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(96 citation statements)
references
References 46 publications
1
93
0
2
Order By: Relevance
“…Carbon dioxide is recognized as the key pollutant of vehicle operation in the road network, which is set as a fundamental index of environmental influence [45]. Furthermore, the carbon emission model of motor vehicles is widely used in recent research, and so we introduced it into the tourism traffic network [46,47].…”
Section: Green Benefitsmentioning
confidence: 99%
“…Carbon dioxide is recognized as the key pollutant of vehicle operation in the road network, which is set as a fundamental index of environmental influence [45]. Furthermore, the carbon emission model of motor vehicles is widely used in recent research, and so we introduced it into the tourism traffic network [46,47].…”
Section: Green Benefitsmentioning
confidence: 99%
“…The electrification of mobility is an essential element in a wider strategy for achieving reduced greenhouse gas emissions [2]. During the previous century, the automotive industry transformed society, bringing new technologies to the market that enhanced their internal combustion engine vehicles, such as global electric vehicles, which are known as one of the most hopeful alternatives for lowering transport-sector carbon dioxide emissions [3,4]. An Electric Vehicle (EV) is a road vehicle that includes electric propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Ellingsen et al (2016) [5] found that when comparing equal vehicle sizes, the EVs have 20-27% lower lifecycle impact than the ICEVs using the average European electricity mix. Using a Monte Carlo method to simulate EVs use-phase under a wide range of driving conditions, Canals Casals et al (2016) [6] calculated the GHG emission associated with EVs and ICEVs for the EVs' top-selling European countries. They found that only France (76% nuclear power energy ratio) and Norway (94% hydropower) ensures global warming potential (GWP) reductions for the whole EVs energy consumption range.…”
Section: Introductionmentioning
confidence: 99%